2006
DOI: 10.1182/blood-2005-12-4828
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine alone and in combination with cyclophosphamide or cyclophosphamide plus mitoxantrone in the treatment of progressive chronic lymphocytic leukemia: report of a prospective, multicenter, randomized trial of the Polish Adult Leukemia Group (PALG CLL2)

Abstract: In this prospective randomized trial, we compared the efficacy and toxicity of cladribine (2-CdA) alone to 2-CdA combined with cyclophosphamide (CC) or cyclophosphamide and mitoxantrone (CMC) in untreated progressive chronic lymphocytic leukemia (CLL). Study end points were complete response (CR), overall response, minimal residual disease (MRD), progression-free survival, overall survival, and toxicity. From January 1, 1998 to December 31, 2003, 508 patients from 15 hematology departments were randomized. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 43 publications
1
59
1
2
Order By: Relevance
“…Consequently, minimal residual disease (MRD) assessments during and after therapy gained importance to individualize therapy 6,9,15,16 and to measure efficacy of novel therapeutic approaches. 4,5,17,18 Although exclusively qualitative and rather insensitive techniques for MRD assessments such as consensus primer IGH PCR 4,10,12,19 or CD19/CD5 dual staining by flow cytometry 5,20,21 are still being used, sensitive MRD quantification requires either specialized four-color flow cytometry (MRD flow) or allelespecific oligonucleotide primer IGH RQ-PCR (ASO IGH RQ-PCR). There is evidence that even qualitative MRD methods can provide prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, minimal residual disease (MRD) assessments during and after therapy gained importance to individualize therapy 6,9,15,16 and to measure efficacy of novel therapeutic approaches. 4,5,17,18 Although exclusively qualitative and rather insensitive techniques for MRD assessments such as consensus primer IGH PCR 4,10,12,19 or CD19/CD5 dual staining by flow cytometry 5,20,21 are still being used, sensitive MRD quantification requires either specialized four-color flow cytometry (MRD flow) or allelespecific oligonucleotide primer IGH RQ-PCR (ASO IGH RQ-PCR). There is evidence that even qualitative MRD methods can provide prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of effective treatments subsequent to disease progression therefore plays an important role in the association between endpoints, because a long post-progression period adds randomness that attenuates the ability to detect os benefits. In the context of cll, studies in previously untreated patients receiving a first-line treatment often show a statistically significant improvement of pfs, but not of os 37,[41][42][43][44][45][46][47][48] . In fact, in studies assessing first-line treatment, the time from first therapy to final endpoint is often long enough to introduce confounding factors such as crossover and subsequent-line therapies, leading to a statistically nonsignificant difference in os.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent analysis of the subgroup of patients without high-risk genetic deletions in the CLL4 trial of the German Chronic Lymphocytic Leukemia Study Group showed that FC did prolong the OS in these patients when compared with fludarabine monotherapy. 25 One trial of cladribine (C) versus cladribine and cyclophosphamide (CC) versus cladribine, cyclphosphamide plus mitoxantrone 26 showed superior CRs for the cyclphosphamide plus mitoxantrone arm over C but not the CC arm (Table 6). …”
Section: Combining Purine Analogs With Alkylating Agentsmentioning
confidence: 99%
“…24 and median. 26 ineffective, whereas lower dose (20 mg/m 2 thrice weekly) has X50% epitope retention and better clearance of leukemia cells with subsequent rituximab infusions. 36 These interesting and provocative data warrant further investigation.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%